2020
DOI: 10.18352/lq.10314
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and beliefs of academic librarians in Germany and the USA: a comparative study

Abstract: The purpose of this study is to understand, compare, and contrast professional experiences, attitudes, and beliefs among personnel in academic libraries in the USA and in Germany, which may inform future library and librarian collaborations between the two countries. Notable findings include differences in: respondents' professional backgrounds; services offered by, and perceived adequacy and support of, respondents' libraries; and views of the library profession and its future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The literature identifies the common approaches to manage change in libraries include strategic plans, systematic implementation (Sanches, 2018), input from library users and these stockholders, effective communication and collaboration (Malenfant, 2010;Phillips, 2014), future planning and improvement (Tam and Robertson, 2002;Wong, 2019). As Pryce-Jones (2018) stated that the library professionals need to change library mission in the UK and Germany, at the same time Kramer and Horstmann (2019) identified to create a clear vision and mission for academic libraries in the USA and Germany to survive and grow in a competitive age. Diversity is also one of the issues in the discussion for the past three decades and it covers several topics such as innovative technology, a wide range of resources and modern facilities for the academic community (Charney and Hauke, 2020;Ippoliti et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature identifies the common approaches to manage change in libraries include strategic plans, systematic implementation (Sanches, 2018), input from library users and these stockholders, effective communication and collaboration (Malenfant, 2010;Phillips, 2014), future planning and improvement (Tam and Robertson, 2002;Wong, 2019). As Pryce-Jones (2018) stated that the library professionals need to change library mission in the UK and Germany, at the same time Kramer and Horstmann (2019) identified to create a clear vision and mission for academic libraries in the USA and Germany to survive and grow in a competitive age. Diversity is also one of the issues in the discussion for the past three decades and it covers several topics such as innovative technology, a wide range of resources and modern facilities for the academic community (Charney and Hauke, 2020;Ippoliti et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, many intellectuals constantly stressing on the present and future challenges of libraries and indicating about high qualities of leadership and effective skills for the academic libraries (Konya and Gurel, 2014;Schulte et al, 2018;Wong, 2019). In fact, diversity has created challenges and anxiety among library professionals (Phillips, 2014), it is not easy to manage change while organizations facing a financial crisis, restructuring their policies and preparing themselves for the upcoming challenges (Charney and Hauke, 2020;Kramer and Horstmann, 2019). According to Meulemans and Maltin (2019), the twenty-first century has already brought many changes in libraries such as users' expectations, collaboration with stakeholders, technological advancement, offer a wide range of resources that are difficult to manage (Young et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As Cummings and Worley (2009: 165) described that leaders must pay careful attention to all steps and actions at the time of developing and introducing change. In terms of academic libraries, changes are the key issues for library professionals and many scholars continuously focusing on the current situation such as selection and collection development of digital resources (Kramer and Horstmann, 2019), virtual and physical library spaces (Grant, 2018) and discussing the future scenarios of libraries (Tam and Robertson, 2002; Stephens and Russell, 2004; Konya and Gurel, 2014; Schulte et al , 2018). Similar challenges and issues have also been reported by the Association of College and Research Libraries (ACRL Research Planning and Review Committee, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pryce-Jones (2018) reported that library professionals facing challenges where organizational restructuring has brought numerous changes an increasing demand of patrons, changes in institutional policies and mission statements (Kramer and Horstmann, 2019; Meulemans and Maltin, 2019). Grant (2018) reported that libraries need effective ways of working, a wealth of resources and innovative physical library facilities, these realities require adapting changes for survival and growth (Pryce-Jones, 2018; Popp, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%